Peran Pemuda terhadap Pembangunan Desa melalui Program Karang Taruna di Desa Karangpoh, Jatinom-Klaten - Prasetio Ariwibowo (LITERATUS, 2020)
The purpose of this study was to determine youth participation in the Karang Taruna Desa program in terms of program management aspects and to find out the inhibiting and supporting factors of youth participation in the Karang Taruna village program. This research uses a qualitative approach with descriptive methods, data collection techniques carried out by interview, observation, and documentation. The validity of the data used is data triangulation, namely source triangulation. The data analysis technique is qualitative descriptive with the following stages: data collection, data reduction, presentation and conclusion drawing. The results obtained in this study (1) youth participation in the Karang Taruna village program viewed aspects of program management using four stages of participation, namely participation in planning; participation in implementation and participation in utilization; (2) factors that hamper youth participation in the Youth Organization program are limited time from individuals and lack of confidence to channel their potential. While the supporting factors are that individuals have high social awareness or spirit to build community through the Youth Organization program.